Fighting the Giants: Efforts in Holding Corporation Responsible for Environmental Damages in Indonesia - Arie Afriansyah; Anbar Jayadi; Angela Vania (Faculty of Law, Hasanuddin University, 2018)
This paper focuses on examining environmental cases before the Indonesian courts from the past ten years. To be specific, this paper will study four major cases with regard private law, six major cases with regard to criminal law, and class action cases in Indonesia. This period of time explains trending increase of environmental cases before the courts. In this regard, Alternative Dispute Resolution (ADR) becomes the main preference of settling the environmental disputes. However, ADR seems not able to bring justice to the fullest especially when it comes to the corporations. It is not justice to the fullest in the sense that there seems no deterrence ADR brings to the corporations when the corporations do indeed damages the environment. As the environmental awareness increases and at the same time, ADR seems fail to fulfill the expectation to save the environment, another way to bring justice emerges namely through various efforts in lawsuits. Nevertheless, such lawsuits are not perfect as there are varieties of results from Indonesian courts. This paper argues that such variety of decisions have been heavily influence by the availability of scientific data and the knowledge of the panel of judges. Specifically, in the case of class action lawsuit, those who defend the environment has limitation on resources usually initiate such lawsuit. Whereas, corporation that being sued is relatively have the capacity to face the trial due to its high financial resources. Nevertheless, “fighting the giants” has been the paradigm when it comes to pursue the responsibility of corporation of its wrongdoing especially environmental damages.